(untitled) (Research, Society and Development, 2024)
Congenital syphilis is a notifiable disease and a preventable cause of death and malformations. Despite observable advancements, the trajectory of detection rates continues to ascend, failing to meet the targeted objective of disease elimination. The primary objective of this article is to analyze the rates of laboratory follow-up. This article is an observational descriptive retrospective study, based on the analysis of antenatal records of syphilis-positive pregnant women and their neonates, delivered at Hospital Municipal Universitário de Taubaté from January 2017 to January 2019. The sample is composed of 38 gestations, resulting in 29 live births. Upon discharge, 96.5% were directed to seek consultation with an Infectious Disease specialist; 48.2% of those referrals did not attend any consultation. 36% completed two negative and consecutive non-treponemal tests and were discharged from the laboratory follow-up, and 13,8% had a treponemal test after 18 months. No documentation pertaining to referrals or counter-referral exchanges with primary care providers was evident within the medical records of patients from Taubaté. In conclusion, there are high abandonment and low adequate follow up rates. Moreover, it is notorious the lack of engagement by primary care services in the surveillance of congenital syphilis, in addition to the lack of an integrated facilitating system to coordinate the data between primary care and specialized professionals, which compromises the integral care of the patient.